ACR–ASTRO Practice Parameter for Image-guided Radiation Therapy (IGRT). (July 2020) - Luh, Join Y.; Albuquerque, Kevin V.; Cheng, Cheewai; Ermoian, Ralph P.; Nabavizadeh, Nima; Parsai, Homayon; Roeske, John C.; Weiss, Stephanie E.; Wynn, Raymond B.; Yu, Yan; Rosenthal, Seth A.; Hartford, Alan
Abstract : Aim/Objectives/Background: The American College of Radiology (ACR) and the American Society for Radiation Oncology (ASTRO) have jointly developed the following practice parameter for image-guided radiation therapy (IGRT). IGRT is radiation therapy that employs imaging to maximize accuracy and precision throughout the entire process of treatment delivery with the goal of optimizing accuracy and reliability of radiation therapy to the target, while minimizing dose to normal tissues. Methods: The ACR–ASTRO Practice Parameter for IGRT was revised according to the process described on the ACR website ("The Process for Developing ACR Practice Parameters and Technical Standards, " www.acr.org/ClinicalResources/Practice-Parametersand-Technical-Standards ) by the Committee on Practice Parameters of the ACR Commission on Radiation Oncology in collaboration with the ASTRO. Both societies then reviewed and approved the document. Results: This practice parameter is developed to serve as a tool in the appropriate application of IGRT in the care of patients with conditions where radiation therapy is indicated. It addresses clinical implementation of IGRT including personnel qualifications, quality assurance standards, indications, and suggested documentation. Conclusions: This practice parameter is a tool to guide clinical use of IGRT and does not make recommendations on site-specific IGRT directives. It focuses on the best practices and principles to consider when using IGRT effectively, especially with the significant increase in imaging data that is now available with IGRT. The clinical benefit and medical necessity of the imaging modality and frequency of IGRT should be assessed for each patient.